The RITMARE Italian Fixed-Point Observatory Network (IFON) for marine environmental monitoring: a case study. (12th February 2016) - Ravaioli, M.; Bergami, C.; Riminucci, F.; Langone, L.; Cardin, V.; Di Sarra, A.; Aracri, S.; Bastianini, M.; Bensi, M.; Bergamasco, A.; Bommarito, C.; Borghini, M.; et al.
ABSTRACT: The Italian Fixed-Point Observatory Network (IFON) integrates well-established coastal and ocean infrastructures (buoys, platforms, moorings, mast platforms, etc.), most of them providing real-time multidisciplinary monitoring for a number of marine and atmospheric variables. Here, we describe the network characteristics and then discuss an example of its operation during the cold spell of winter 2012. One of the goals of the Italian Flagship Project Ricerca Italiana per il mare (RITMARE) is to create a common, validated IFON database able to fulfil both public and private demands, including validation of remotely sensed data and numerical models, environmental planning and management, and time-series analysis of climate and oceanographic data.